PENGARUH PROSES REKRUTMEN DAN SELEKSI KERJA TERHADAP PENGEMBANGAN KARIR KARYAWAN PADA PT SIANTAR TOP TANJUNG MORAWA - Rifki Arya Akbar; Amirudin Amirudin (JURNAL MANAJEMEN DAN BISNIS, 2022)
determine the effect of job selection on Career Development and determine the effect of the Recruitment and Job Selection Process simultaneously on Career Development at PT Siantar Top Tanjung Morawa. This quantitative descriptive research with a questionnaire instrument was conducted on a population of 65 people, determining the sample using a saturated sample so that the research sample was as much as. 65 people. The results showed that the tcount coefficient for the Recruitment Process was 6623, the ttable value was 2.748, the tcount > ttable (6,623 > 2,748 ) and the sig value < 0.05 (0.000 < 0.05), the tcount coefficient for Job Selection was 6.486 and the ttable value was 2.748, the value tcount > ttable (6,486 > 2,748 ) and sig < 0.05 (0.000 < 0.05). Furthermore, the F value of the Recruitment and Job Selection Process is 15,727 and the value of sig is 0.000, whereas, the value of Ftable is 1.997 then Fcount > Ftable or (15,727 > 1.997 ) and the value of sig < 0.05 (0.000 < 0.05). The value of RSquare is 0.835 or R2 x 100% of 83.50%, meaning that the recruitment and job selection process makes a major contribution to explaining Career Development at PT Siantar Top of 83.50% while the remaining 13.50% is another factor. The conclusion of the study is that the recruitment process has a significant effect on Career Development, Job Selection has a significant effect on Career Development, and the Recruitment and Job Selection Process simultaneously has a significant effect on Career Development at PT Siantar Top Tanjung Morawa.